The role of community based organisations' NGOs and farmers in technology transfer - Jeremiah, S.C.; Kulembeka, H.P.; Kanju, E.; Chirimi, B.; Amour, R. (International Society for Tropical Root Crops, 2007)
Cassava (Manihot esculenta Crantz) and sweetpotato (Ipomoea batatas) are key food crops in Tanzania in general and in the lake zone in particular. Cassava and sweetpotato are household food security crops in addition to being a source of household income. Availability of the new improved varieties to farmers has been a problem in Tanzania. A project was initiated to transfer improved varieties of both cassava and sweetpotato in the lake zone to farmers. In collaboration with community-based organisations (CBOs), non-government organisations (NGOs) and farmer groups, the project distributed different varieties of cassava and sweet potato in Shinyangu and Mwanza regions through CIP/ASARECA. The CBOs, NGOs and farmer groups were very instrumental in facilitating the delivery of improved varieties to farmers. Through this informal seed delivery system using CBOs, NGOs, and farmers groups, farmers have been able to access, use and adopt improved varieties suitable for their areas. The project has also established a system that can be used for future technology transfer activities. through this system more than 988,000 and 1,752,711 cuttings of improved cassava and sweet potato varieties respectively were distributed in three regions of the lake zone. The distribution activity went hand in hand with training of farmers in rapid multiplication techniques of planting materials.